Malaria and HIV/AIDS Coinfection in Patients Under Highly Active Antiretroviral Therapy at the Regional Hospital of Bafoussam (West Cameroon) - Romeo Tankoua-Tchounda; Jacques Nack; Christian Mbohou Nchetnkou; Desire Leonard Keptcheu Tchankwe; Michel Lontsi-Demano; Estelle Essangui; Alex Kevin Tako Djimefo; Leopold Gustave Lehman (Journal of Parasitology Research)
Conclusion: This study showed that HIV+ patients were carriers of Plasmodium falciparum and Plasmodium vivax with an appreciable overall prevalence. The only factor influencing the prevalence of malaria was using traditional medicine.